The EU as a Global Actor : Space Policy - Heřmánek, Jakub; Machoň, Miloslav, 1988-; Zemanová, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The thesis topic is the EU’s global actorship status in the field of space policymaking. The thesis aims to evaluate the EU’s role in European space policymaking. The individual actor’s legitimacy, influence, and interest define the actor’s role. The thesis utilizes the qualitative content analysis to interconnect the coding’s results better, using the grounded theory. The thesis’s result is the EU’s relevance outline and the question’s answer regarding the EU’s legitimacy in European space policymaking.
Vedoucí práce: Miloslav Machoň
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses